If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9 + 5n + 7 = 0 Reorder the terms: -9 + 7 + 5n = 0 Combine like terms: -9 + 7 = -2 -2 + 5n = 0 Solving -2 + 5n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 5n = 0 + 2 Combine like terms: -2 + 2 = 0 0 + 5n = 0 + 2 5n = 0 + 2 Combine like terms: 0 + 2 = 2 5n = 2 Divide each side by '5'. n = 0.4 Simplifying n = 0.4
| 2r+8-5= | | -2m-5-2(m-2)=3m-(4m-6)-5m+1 | | 2n+2(n+7)+1=39 | | 2y+2(y+1)=-6 | | 85+55x=y | | y=120+16(x) | | 2-6=a+a+4 | | -4p-3(4-3p)=2(p-4)-22 | | 3r+5(r-1)=27 | | 5(x+3)=8(x+6) | | 14x+12=4x^2 | | 4(r+6)=-49 | | -8x+48=-2(x-2)(x-2)+32 | | X+-1=0 | | -3(r+7)=-40 | | X+-2=0 | | 10(v+2)-2v=2(4v+3)-9 | | 2.87x+25.83=51.66 | | 5r^2=48+r | | -4(r+3)=-61 | | -10x+4=-7x+13 | | 9y-7=28 | | 6(x-2)=(x-4)-28 | | .3x+5=x+3 | | 18x-30= | | .3x+.5=1-0.05x | | f(X)=x^2+6x+1 | | (2x+10)+(6x-4)= | | -7-3y=14 | | 10+25b= | | 8w-6.4=-6.4+5w | | x^2-26x+138=0 |